Hyperfictional Language in Michael Joyce’s Afternoon, a Story and Megan Heyward’s of Day, of Night (2012)
The hypertext, a relatively new digital genre, structures texts into links and nodes. This results in textual plasticity which gives room for different forms of stylistic experimentations by the authors of the texts. While scholars have focused on the structural composition and general nature of hypertexts, they have not adequately attended to their distinctive features. This study addresses this neglect by examining the style of the language of hyperfiction. The study adopts Hallidayan model of Systemic Functional Linguistics, complemented with Postmodern Literary Theory and Applied Media Aesthetics, which respectively account for grammatical categories, stylistic experimentations, and audio-visual effects. Two CD-ROM-based hyperfiction texts, namely, Michael Joyce’s afternoon, a story and Megan Heyward’s of day, of night, available only in the United States of America, are purposively selected and their verbal and non-verbal levels are explored. The data are subjected to content analysis. At the stylistic experimentation level, both hyperfiction texts exhibit similar stylistic features in terms of fragmentation of text units, playfulness in presentation styles, and deconstruction of linear temporal deixis. Beyond these features, the authors explore the architecture of nodes and links in providing the texts with alternative reading paths that resist the sense of definite closure in meaning-making. In Joyce’s afternoon, a story, the alternative reading paths locate meaning within unstable contexts of situation, with the paths, sometimes, negating one another. This situation gives way to contradictory narrative turns which project a resistance to the sense of closure and accomplish postmodernist aesthetics of self-cancellation and projected-world erasure. In Heyward’s of day, of night, the existence of multiple endings and the highly interactive nature of the narrative facilitate the text’s resistance to closure. At the grammatical level, Joyce’s afternoon, a story is categorised as a complex text because of the vast employment of word and group nexuses, internal nesting and rankshifted, verbless, and complex clauses. The grammatical complexity in the text depicts postmodernist attempts at foregrounding the processes of meaning construction and the writtenness of the text. In of day, of night, though Heyward mainly employs simple clauses, her employment of incomplete clauses as node titles in the “night” part of the text indicates a resistance to closure as well as an attempt at problematising meaning. In terms of audio-visual effects, afternoon, a story does not engage any media aesthetic effect because it is basically alphanumeric. However, Heyward appropriates media aesthetics such as saturation/desaturation, superimposition, imbalance screen resolution, and music/sounds for advancing and intensifying the narrative of the multimodal of day, of night. This multimodal nature of of day, of night portrays collage and the carnivalistic tendencies in postmodernist aesthetics. The hypertextual stylistic resources deployed in Joyce’s afternoon, a story and Heyward’s of day, of night define the postmodernist nature of the texts. The creative manipulations of linguistic and non-linguistic elements in the two texts draw attention to how hyperfiction writing is expanding the concepts of text and language. Stylisticians need to investigate digital texts in order to understand how digital writing tradition is redefining linguistic and literary representations.